Analisis IT Service Management (ITSM) dengan Framework ITILV4 di Universitas Islam Negeri Raden Fatah Palembang - Citra Suryanto; Mulyati Mulyati (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to analyze the implementation of Information Technology Service Management (ITSM) using the Information Technology Infrastructure Library (ITIL) version 4 framework at Universitas Islam Negeri Raden Fatah Palembang. Along with the increasing reliance of higher education institutions on information technology to support academic and administrative activities, structured, effective, and value-oriented IT service management is essential. Common issues such as disruptions to information system services and delays in incident handling have become critical reasons for evaluating the existing IT service management practices. This research focuses on the Service Management Practice domain, particularly Incident Management and Problem Management practices, as both play a strategic role in maintaining service continuity and preventing the recurrence of similar disruptions. The research method employed is descriptive quantitative, with data collected through questionnaires distributed to students, lecturers, and information technology staff as users and managers of IT services. The collected data were then analyzed using maturity level measurements based on ITIL V4 and complemented by gap analysis to identify discrepancies between the current conditions and the expected conditions. The results indicate that the maturity level of IT service management is at Level 4 (Managed), suggesting that service processes are well-defined, managed, and monitored through clear performance indicators. Nevertheless, several aspects still require improvement to ensure that IT service management can achieve an optimal and sustainable level. Therefore, this study provides a set of strategic recommendations that are expected to serve as a reference for the university in enhancing the quality of IT services and strengthening overall information technology governance.